2021
DOI: 10.1038/s41467-021-23440-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 outbreaks and interventions on influenza in China and the United States

Abstract: Coronavirus disease 2019 (COVID-19) was detected in China during the 2019–2020 seasonal influenza epidemic. Non-pharmaceutical interventions (NPIs) and behavioral changes to mitigate COVID-19 could have affected transmission dynamics of influenza and other respiratory diseases. By comparing 2019–2020 seasonal influenza activity through March 29, 2020 with the 2011–2019 seasons, we found that COVID-19 outbreaks and related NPIs may have reduced influenza in Southern and Northern China and the United States by 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
175
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(203 citation statements)
references
References 31 publications
27
175
1
Order By: Relevance
“…The current preliminary findings reaffirm the usefulness of the NPI measures recommended by WHO and remind us of the need and importance of educational campaigns and the practical implementation of public health policies. In particular, with a continuous circulation of COVID-19 and use of NPIs in many countries, detailed studies are critically needed to evaluate the causes of decreased respiratory infections [ 89 91 ]. Additionally, until viable pharmaceutical options for HRSV become available, it is important to continue to evaluate non-pharmaceutical strategies and their potential benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The current preliminary findings reaffirm the usefulness of the NPI measures recommended by WHO and remind us of the need and importance of educational campaigns and the practical implementation of public health policies. In particular, with a continuous circulation of COVID-19 and use of NPIs in many countries, detailed studies are critically needed to evaluate the causes of decreased respiratory infections [ 89 91 ]. Additionally, until viable pharmaceutical options for HRSV become available, it is important to continue to evaluate non-pharmaceutical strategies and their potential benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the context of this research, we observed that the main focus of the tweets related mainly to COVID-19 pandemic events (disease, confinement, politician talks, vaccines approval, and vaccination) and increased over time, like the prevalence of the terms “vaccines” and “vaccination,” and this was in contrast with the term “flu,” which disappeared over time from the tweets. This reflects that COVID-19 measures, such as social distancing and mask wearing, significantly reduced the seasonal influenza rates in 2020-2021 [ 73 , 90 , 91 ]. However, a potential major reason and mechanism of these changes in trends and therefore of the folksonomy content may be associated with the diversion of citizens’ attention to annual influenza spread, caused by the disruptive and menacing COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 91%
“…Starting from January 2020, people were asked to wear masks in crowded closed places and public places, reduce participation in non-essential gatherings, and maintain a social distance of more than 1 meter. All provinces in mainland China adopted stringent public health measures from January 2020 ( 11 ). Taking Wuhan as an example, on January 14, 2020, the government implemented the entry and exit policy, and established temperature detection points in public places.…”
Section: Introductionmentioning
confidence: 99%